2021
DOI: 10.3390/diagnostics11030517
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Histone Deacetylase (HDAC)-1, -2, -4 and -6 Expression in Salivary Gland Tumors

Abstract: Salivary gland tumors (SGTs) comprise a group of rare neoplasms. Locally aggressive, recurrent and/or metastatic SGTs are notorious for their resistance to systemic therapy, making the need for carefully designed, prospective and randomized trials with useful predictive markers mandatory to define new effective therapeutic protocols. Histone Deacetylases (HDACs), are thought to play a crucial role in carcinogenesis. They affect the DNA structure, being also able to regulate its transcription, repair, and repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 64 publications
(51 reference statements)
0
22
1
Order By: Relevance
“…In the last decade, HDACs have been suggested to play a crucial role in the regulation of cell proliferation, differentiation, and apoptosis in various human hematological, solid, and mesenchymal malignancies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. HDAC IHC expression has been described in several tumor types, being associated with important clinicopathological parameters, including patients’ prognosis [ 18 , 19 , 20 , 22 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, HDACs have been suggested to play a crucial role in the regulation of cell proliferation, differentiation, and apoptosis in various human hematological, solid, and mesenchymal malignancies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. HDAC IHC expression has been described in several tumor types, being associated with important clinicopathological parameters, including patients’ prognosis [ 18 , 19 , 20 , 22 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Red chromogen visualization kit enabled visualization in tissues containing a large amount of melanin. Appropriate negative and positive controls were used as appropriate [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…A notable amount of research has been performed regarding HDACs' clinical significance in oral cancer and less in nasopharyngeal cancer and salivary gland tumors [12][13][14][15][16][17][18][19][20][21] (Table 2). HDAC-2 was found to be overexpressed in the majority of cases with epithelial dysplasia and oral squamous cell carcinoma (SCC) without, however, showing any noteworthy correlation with sex, age or oral habits in those patients [20].…”
Section: Nasopharyngeal Cancer Salivary Glands and Oral Cancermentioning
confidence: 99%
“…Another study performed on a series of nasopharygeal cancer (NPC) cases, revealed a positive association among the increased HDAC-4 levels in primary and metastatic NPC tissues with poor overall survival (OS) and progression-free survival (PFS) [18]. Regarding salivary gland tumors (SGTs), the only clinical associations studied are between the expression of HDAC-1, -2, -4 and -6 in both benign and malignant tumors [19]. More precisely, HDAC-2 upregulation was associated with a better OS and prognosis, while HDAC-6 overexpression revealed to be a negative prognosticator of patients suffering from malignant SGTs [19].…”
Section: Nasopharyngeal Cancer Salivary Glands and Oral Cancermentioning
confidence: 99%
See 1 more Smart Citation